Definition of the margin of major coronary artery bifurcations during radiotherapy with electrocardiograph-gated 4D-CT. (May 2018) - Li, Qian; Tong, Ying; Yin, Yong; Cheng, Pinjing; Gong, Guanzhong
Highlights: Cardiac activity is a major source of heart dose variation in thoracic radiotherapy. We determine the margins of coronary bifurcations utilizing electrocardiography-gated 4D-CT. To date, there has been no consensus on the study of the coronary artery margin. The various motion among bifurcations manifested that individual margins should be given. The margins of coronary bifurcations held significant potential for protecting of coronary artery. Abstract: Purpose: The aim was to measure the cardiac motion-induced displacements of major coronary artery bifurcations utilizing electrocardiography (ECG)-gated four-dimensional computed tomography (4D-CT) and to determine the margin of coronary artery bifurcations. Methods: Thirty-seven female patients who underwent retrospective ECG-gated 4D-CT in inspiratory breath hold (IBH) were enrolled. The left main coronary artery bifurcation (LM), the obtuse marginal branch bifurcation (OM), the first diagonal branch bifurcation (D1 ), the second diagonal branch bifurcation (D2 ), the caudal portion of the left anterior descending branch (APX), the first right ventricular artery bifurcation (V) and the acute marginal branch bifurcation (AM) were contoured. The center of the contour of the coronary arterial bifurcations at end systole was defined as the standard, and the margin were then calculated. Results: The margin in the left–right (LR), cranio-caudal (CC), and anterior-posterior (AP) coordinates were as follows:LM 3, 3, and 3 mm;D1 6, 3, and 3 mm;D2 3, 3, and 3 mm;APX 4, 4, and 4 mm;OM 4, 6, and 5 mm;V 6, 8, and 7 mm; andAM 6, 8, and 7 mm, respectively. Conclusion: Coronary artery bifurcations should be considered a separate organ at risk (OAR), and different margin should be provided due to the differences resulting from motion displacement. The maximum margin in the LR, CC, and AP coordinates of left coronary artery bifurcations were 6, 6, and 5 mm, and those of the right coronary artery bifurcations were 6, 8, and 7 mm, respectively.